2020
DOI: 10.1017/s1368980020004553
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and sleep quality: a community-based study

Abstract: Objective: To assess the association between total alcohol intake, specific alcoholic beverages, and sleep quality in a community-based cohort. Design: A cross-sectional study. Setting: The Kailuan community, China. Participants: Included were 11,905 participants who were free of a history of cardiovascular diseases, cancer, Parkinson’s disease, dementia, and head injury in or prior to 2012. Alcohol consumption (amount and frequency intake) and alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 28 publications
2
34
0
1
Order By: Relevance
“…Current smoking, alcohol drinking and chronic diseases were also not found to be associated with insomnia in the present study. Recently, a meta-analysis and a large-scale community-based cohort study demonstrated that smoking and higher alcohol consumption was associated with poorer sleep quality and insomnia [ 40 , 41 ]. However, neither of these two studies investigated the subgroup of older adults, even though the population in both studies included older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Current smoking, alcohol drinking and chronic diseases were also not found to be associated with insomnia in the present study. Recently, a meta-analysis and a large-scale community-based cohort study demonstrated that smoking and higher alcohol consumption was associated with poorer sleep quality and insomnia [ 40 , 41 ]. However, neither of these two studies investigated the subgroup of older adults, even though the population in both studies included older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The global prevalence of hypertension has shown an upward trend, from 17.3% in 1990 to 20.5% in 2015. 1 2 In China, it is estimated that 245 million adults have hypertension, accounting for 23.2% of the total. 3 Hypertension can lead to numerous adverse health outcomes, such as cardiovascular and cerebrovascular diseases and premature death.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is a worldwide public health issue. The global prevalence of hypertension has shown an upward trend, from 17.3% in 1990 to 20.5% in 2015 1 2. In China, it is estimated that 245 million adults have hypertension, accounting for 23.2% of the total 3.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, menopause-related symptoms also greatly influenced sleep quality ( Pien et al, 2008 ). Hypertension, hyperlipidemia, diabetes, and alcohol consumption were associated with poor sleep quality ( Chiang et al, 2018 ; Wang et al, 2020 ; Zheng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%